Broadly reactive aptamers targeting bacteria belonging to different genera using a sequential toggle cell-SELEX - Song, Min Young; Nguyen, Dung; Hong, Seok Won; Kim, Byoung Chan (NATURE PUBLISHING GROUP, 2017)
Conventional cell-SELEX aims to isolate aptamers to a single unique target bacteria species. We propose a method to isolate single-stranded DNA aptamers that have broad reactivity to multiple bacterial targets belonging to different genera. The key of the proposed method is that targets of interest are changed sequentially at each SELEX round. The general scheme was examined using six bacteria from different genera, Escherichia coli, Enterobacter aerogenes, Klebsiella pneumoniae, Citrobacter freundii, Bacillus subtilis, and Staphylococcus epidermidis (four gram-negative and two gram-positive bacteria). In the first round of SELEX, the DNA library was incubated with E. coli and amplicons bound to E. coli were separated. The amplicons were sequentially separated by incubation with E. aerogenes, K. pneumoniae, C. freundii, B. subtilis, and S. epidermidis at each SELEX. The amplicons obtained using the last bacterial species were incubated again with the first bacterial species and this loop was repeated two more times. We refer to this method as sequential toggle cell-SELEX (STC-SELEX). The isolated aptamers had dissociation constants of 9.22-38.5 nM and had no affinity to other bacteria that were not included in STC-SELEX. These results demonstrate the potential to isolate aptamers with broad affinity to bacterial taxa in different genera.